PHOSPHOLIPIDS OF FIVE INDIAN FOOD FISHES - GOPAKUMAR, K; NAIR, M RAJENDRANATHAN (Fishery Technology, 2025)
The phospholipids of five Indian food fishes, viz; sardine,pomfret, mackerel, anchovies and thrissodes were fractionatedquantitatively using column and thin layer chromatographictechniques and the results reported in this communication.